2001
DOI: 10.1002/1521-3765(20010316)7:6<1232::aid-chem1232>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Sulfonimidates by Dynamic Diastereomer-Differentiating Cyclisation: Large-Scale Synthesis and Mechanistic Studies

Abstract: A dynamic diastereomer differentiating cyclisation is the key step in a new large-scale synthesis of both enantiomers of the cyclic sulfonimidates 1 (Aldrich no. 54099-4) and ent-1 (Aldrich no. 54412-4). These are valuable starting materials in the asymmetric synthesis of chiral oxa- and azaheterocyclic compounds. NMR spectroscopic studies on the reacting system reveal N-chloro sulfinamides to be reactive intermediates in the oxidative chlorination of sulfinamides with tert-butyl hypochlorite and allow for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…The findings of Johnson7d and Reggelin13 on related systems suggested that the nucleophilic chloride displacement of sulfonimidoyl chlorides 6 and 7 with ammonia occurred with inversion of configuration. In order to confirm this hypothesis and to ensure the stereochemistry of the products it was decided to determine their absolute configuration by experimental and theoretical CD spectroscopy, which allowed establishing the spatial arrangement of the substituents at the chiral sulfur atom with a high degree of probability.…”
Section: Resultsmentioning
confidence: 98%
“…The findings of Johnson7d and Reggelin13 on related systems suggested that the nucleophilic chloride displacement of sulfonimidoyl chlorides 6 and 7 with ammonia occurred with inversion of configuration. In order to confirm this hypothesis and to ensure the stereochemistry of the products it was decided to determine their absolute configuration by experimental and theoretical CD spectroscopy, which allowed establishing the spatial arrangement of the substituents at the chiral sulfur atom with a high degree of probability.…”
Section: Resultsmentioning
confidence: 98%
“…A rearrangement of 53 via a 6-electron transition state allowed access to sulfonimidates 54 with retention of configuration (Scheme 13a). However, from intermediate 53, an alternative route via an three-atom rearrangement (first reported by Reggelin and co-workers) 34 would afford a sulfonimidoyl iodonium 55a species that could be responsible for loss in enantiomeric excess during the transformation, yielding sulfonimidate 56 (Scheme 13b).…”
Section: Synthesis Of Acyclic Sulfonimidates From Sulfinamides Utilising Hypervalent Iodine Species and Applications Towards Sulfoximine mentioning
confidence: 99%
“…Nearly two decades ago, Reggelin shed light on the mechanism believed to be in operation during the synthesis of cyclic sulfonimidates. 34 He found through optimisation reactions that two particular pathways were in operation, depending on the base used in the reaction (Scheme 20). Oxidative cyclisation of an enantiomer of sulfinamide involved two key stereoselective steps; the first process is an oxidative chlorination reaction to afford sulfonimidoyl chloride intermediate 81, that proceeds with retention of configuration at sulfur.…”
Section: Synthesis Of Cyclic Sulfonimidates Via Sulfonimidoyl Chloridesmentioning
confidence: 99%
“…Its reduction and O-protection delivered the TMS-protected amino alcohol rac-6 in good yields. Following the established synthetic procedure developed in our group, 23,24 the cyclic sulfonimidate rac-8 was obtained by sulfinylation and diastereoselective cyclization via the epimers rac-7 in good yield and diastereomeric ratio. After removal of the minor diastereomer by crystallization, the sulfonimidate was opened by methyllithium, the product deprotonated with LiHMDS and treated with another equivalent of rac-8.…”
Section: Scheme 1 Retrosynthetic Analysis Bis(sulfoximine)mentioning
confidence: 99%